Consumer Value Perception Model as Consideration for Fusion Beverage Business Sustainability - Hamdan Hamdan; Indra Raharja; Ridho Rafqi Ilhamalimy; Hapzi Ali (Universitas Mercu Buana, 2022)
This research is about consumers’ perception of value in deciding to consume fusion drinks. Fusion drink is a drink that combines various basic ingredients, such as coffee, sugar, milk, tea, cheese, chocolate, yakult and various other basic ingredients. Perceived value arises when consumers decide to consume fusion drinks. This is because, the value contained when consuming fusion drinks is to get pleasure and happiness from various flavors and aromas, where the benefits obtained from various services and offers, as well as the image of the outlet also provide added value. This study seeks to determine the effect of perceived utility, perceived variation, perceived outlet image, perceived hedonic, and perceived value used to build the research model, by conducting an online survey of how these factors are related. The findings of this study are the perceived utility, perceived variation, perceived outlet image, perceived hedonic, and perceived value have a real relationship in shaping positive attitudes and behavior of consumers in deciding to consume fusion drinks.